Immunohistochemical expression of GFAP, GS, AQP4, ALzheimer-2-astrocytosis and brain ammonia levels in deceased septic patients without liver failure and those with sepsis-associated liver injury - Shulyatnikova, T. V.; Tumanskiy, V. O.; Шулятнікова, Тетяна Володимирівна; Туманський, Валерій Олексійович (My University, 2023)
The aim of the study was to determine the ammonia levels and reactive astroglial changes in the brain of de-ceased septic patients without liver failure and deceased patients with sepsis-associated liver injury. Materials and methods. Sectional material of 40 patients who died from abdominal sepsis was studied. Case histories were analyzed according to the SOFA scale with accent on the brain and liver disfunction confirmation and excluding kidney insufficiency. Septic cases designed two main comparison groups: 1) sepsis without SALI («non-SALI», n = 20); 2) sepsis with SALI («SALI», n = 20). Control group included autopsy material of 30 deceased patients with cardiovascular pathology with no inflammatory, metabolic or toxic comorbidity. In paraffin sections of the postmor-tem brain cortex, white matter, hippocampus, thalamus, striatum, and cerebellum, it was determined: I) immunohisto-chemical expression of GFAP, GS, and AQP4; II) histochemical expression of tissue ammonia with Nessler's reagent according to V. Gutiérrez-de-Juan et al. (2017); III) numbers of Alzheimer type 2 astrocytes (AA2). Results. In the «non-SALI» group, it is found increased level of all the studied parameters: I) elevated GFAP in six brain regions with the highest growth in the cortex – by 8.46 times; II) elevated GS in the thalamus and cerebellum (by 1.96 and 1.29 times, respectively); III) elevated AQP4 in six brain regions with the highest rise in the cortex – by 3 times; IV) elevated histochemical ammonia expression in the thalamus, striatum, and cerebellum (by 1.29, 1.20, and 1.17 times, respectively); V) increased AA2 numbers in the cortex and thalamus (by 2.32 and 1.53 times, respectively). The «SALI» group is characterized by the decreased GFAP expression in six brain regions, with the lowest values in thalamus, striatum, and cerebellum. Herewith, in six brain regions increased levels are typical for: I) GS expression, with maximal aggravation in the cortex and thalamus (by 3.20 and 3.18 times, respectively); II) AQP4 expression, with maximal in-crease in thalamus and white matter (by 4.37 and 4.21 times, respectively); III) histochemical ammonia expression with maximal enhancement in thalamus and cerebellum (by 4.33 and 4.27 times, respectively); IV) severity of AA2-astrocy-tosis with maximal rates in the cortex and striatum (increase by 3.58 and 3.23 times, respectively). Мета. Визначення рівня аміаку та реактивних змін астроглії в ГМ померлих септичних хворих без печінкової недостатності та померлих хворих з сепсис-асоційованим пошкодженням печінки. Матеріали і методи. Досліджено секційний матеріал 40 хворих, які померли від абдомінального сепсису. Виділено 2 групи спостереження: 1) сепсис без САПП («бСАПП», n = 20); 2) сепсис із САПП («САПП», n = 20). Імуногістохімічно визначали експресію GFAP, GS і AQP4, гістохімічно – експресію тканинного аміаку з реактивом Несслера і підрахо-вували кількість астроцитів Альцгеймера 2 типу (АА2) у корі та білій речовині ГМ, гіпокампі, таламусі, смугастому тілі та мозочку. Результати. У групі «бСАПП» підвищується експресія GFAP та AQP4 у 6 відділах ГМ, GS – у та-ламусі та мозочку; експресія аміаку – в таламусі, смуастому тілі та мозочку; кількість АА2 підвищується у корі та таламусі. У групі «САПП» у 6 відділах ГМ відзначається падіння експресії GFAP при одночас-ному підвищенні рівнів: GS (максимально – в корі і та-ламусі), AQP4 (максимально – в таламусі і білій речо-вині), аміаку (максимально – в таламусі та мозочку) та вираженості АА2-астроцитозу (максимально – в корі та смугастому тілі).
ммуногістохімічна експресія GFAP, GS, AQP4, Альцгеймер-2-астроцитоз і рівень аміаку в мозку померлих хворих на сепсис без печінкової недостатності і померлих з сепсис-асоційованим пошкодженням печінки
Shulyatnikova T. V. - ORCID ID: 0000-0002-0196-9935; Tumanskiy V. O. - ORCID ID: 0000-0001-8267-2350.
Keywords: sepsis-associated liver injury; brain; immunohistochemistry; ammonia; Alzheimer type 2 astrocytes; сепсис-асоційоване пошкодження печінки; головний мозок; імуногістохімія; аміак; астроцити Альцгеймера 2 типу